Noseworthy, Mamiellen. A mat hooking tool that Mamielle Noseworthy uses for her hooked mats, Lower Cove. - Wilson, Lisa (2010)
A mat hooking tool that Mamielle Noseworthy uses for her hooked mats, Lower Cove.